Gold-Catalyzed Synthesis of Quinolines from Propargyl Silyl Ethers and Anthranils through the Umpolung of a Gold Carbene Carbon - Jin, Hongming; Tian, Bin; Song, Xinlong; Xie, Jin; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K. (Angewandte Chemie International Edition, 2016)
A gold‐catalyzed cascade annulation of propargylic silyl ethers with anthranils proceeds through a sequential ring opening/1,2‐H‐shift/protodeauration/Mukaiyama aldol cyclization. This method offers a regiospecific and modular access to 2‐aminoquinolines and other quinoline derivatives under mild conditions and with a broad functional‐group tolerance. The conversion is possible on a gram scale, which underlines the synthetic practicability of this methodology. The versatility of the obtained scaffold has been demonstrated by useful postfunctionalization. All together now: A gold‐catalyzed cascade annulation of propargylic silyl ethers with anthranils proceeds through a sequential ring opening/1,2‐H‐shift/protodeauration/Mukaiyama aldol cyclization. This method offers regiospecific and modular access to 2‐aminoquinolines and other quinoline derivatives under mild conditions and with a broad functional‐group tolerance.